Stop! Marriage at Child Age - Nenden Dewianti; Rismayanti Dewi; Nursahidin Nursahidin; Aghnia Dian Lestari (Asian Journal of Social and Humanities, 2024)
Marriage at a young age remains a significant social issue requiring special attention, particularly in Indonesia. This study aims to analyze the implementation of the Child Marriage Prevention Policy in Majalengka Regency, as regulated by Regent Regulation Number 54 of 2021, which focuses on the prevention of child marriages. The research employs a qualitative descriptive method, utilizing primary and secondary data sources through observation, interviews, and documentation. The findings reveal that the rate of child marriages in Majalengka Regency is still increasing, despite the government's efforts to implement preventive measures, including socialization strategies aimed at reducing the incidence of child marriages. One of the main challenges in effectively preventing child marriages is the limited human resources available for implementing the program. This research highlights the need for strengthened resources and better coordination among stakeholders to effectively reduce the prevalence of child marriages in the region. The study also suggests that additional interventions, such as enhanced education and community involvement, are essential to complement the ongoing efforts and address this persistent issue comprehensively.